Dari Otoritas Menuju Autentisitas: Rekonstruksi Teologi Postmodern bagi Generasi Z di Era Digital - Lie Kwet Yun Robert Lie (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the transformation of theological authority in the digital era, with a specific focus on Generation Z living within a postmodern socio-cultural context in Indonesia. The research explicitly seeks to (1) identify shifts in the sources of theological authority, (2) examine the forms of digital religious expression adopted by Generation Z, and (3) assess the implications of these shifts for contemporary theological discourse. Employing a qualitative phenomenological approach, the study explores lived religious experiences as they manifest in digital spaces. Data are collected through an extensive literature review and systematic observation of digital faith practices, including online prayer communities, spiritual podcasts, and religious content disseminated through social media platforms. The analytical framework is grounded in the theoretical perspectives of MacGregor, Drilling, and Schindler, which are then contextualized and critically compared with empirical phenomena found in local Indonesian digital spiritual communities. The scope of the study is limited to non-institutional, digitally mediated religious practices among Generation Z, emphasizing how meaning-making processes occur outside formal religious structures. The findings reveal that Generation Z does not disengage from religious belief; rather, they reinterpret faith through more personal, reflective, and dialogical modes of engagement. Authority is increasingly derived from narrative authenticity, peer interaction, and experiential resonance instead of solely from traditional religious institutions. This study contributes theoretically by enriching discussions on theological authority in postmodern digital contexts and practically by offering insights for religious institutions and educators to engage Generation Z more effectively.